(3GdTGQI (B2218 (3ShCdkG h LhGHkG aj GdKbGaI h GdJQGK (B- (3GdLR GdChd (B/ (3LR GdCqhd s - (3GdegjQj, SYjO Hf cQGR s; Saeed bin Karaz AlMheiri (Abu Dhabi Authority For Culture And Heritage, 2011)
Q & A in culture and heritage
Title translation: Emblem 2218- Questions and answers in culture and heritage- Saeed bin Karaz AlMheiri
Arabic
Keywords: HN50-995 Social history and conditions. Social problems. Social reform- By region or country UAE